A triple-drug combination induces apoptosis in cervical cancer-derived cell lines - Delgado-Waldo, Izamary; Contreras-Romero, Carlos; Salazar-Aguilar, Sandra; Pessoa, João; Mitre-Aguilar, Irma; García-Castillo, Verónica; Pérez-Plasencia, Carlos; Jacobo-Herrera, Nadia Judith (Frontiers in Oncology, 2023)
Cervical cancer is a worldwide health problem due to the number of deaths caused by this neoplasm; in 2020 estimated 30,000 deaths in Latin America were reported for this type of tumour. Treatments used to manage patients in early stages have excellent results as measured by different clinical outcomes. However, for locally advanced and advanced stages of the disease, survival rates are quite poor and highly recurrent. It is therefore a priority to develop new therapies or drug combinations that demonstrate greater efficacy in reducing tumour activity. In this sense, it has recently been demonstrated that some drugs used in other pathologies have anti-tumour activity; such is the case of Metformin and Sodium Oxamate. In this research, we combined the drugs metformin and sodium oxamate with doxorubicin (triple therapy or TT) based on their mechanism of action and previous investigation of our group against three CC cell lines. By means of flow cytometry, western blot, and protein microarrays experiments, we found that the TT was able to induce apoptosis on HeLa, CaSki, and SiHa through the caspase 3 intrinsic pathway, including the critical proapoptotic proteins BAD, BAX, cytochrome-C, and p21. Also, the mTOR and the S6K phosphorylated proteins were inhibited in the three cell lines. Moreover, we demonstrate the anti-migratory activity of the TT, suggesting another target of the drug combination in late CC stages. These results, These results together with previous studies of our group allow us to conclude that TT inhibits the mTOR pathway leading to cell death by apoptosis, in addition we demonstrate that this pharmacological combination is able to inhibit tumor cell migration. Our work provides new evidence of TT against cervical cancer as a promising antineoplastic therapy